Intercultural Competences: Impacts of the Workshop “Communicating” on Intercultural Sensitivity of University Teachers - Ayala-Asencio, Carlos Enrique (Revista Electrónica Educare, 2020)
This research aimed to find out the impacts of the “Communicating” Workshop on the dimensions of consciousness, ability, and sensitivity of the intercultural competences of the teaching staff of a professional academic area of a private university in Lima - 2018, in order to develop their intercultural competences contributing to teacher training, in such a way that the teaching to be developed for the student body achieves the educational quality objectives. The methodology was based on the positivist model, with a quantitative approach, of the applied type, with an experimental-quasi-experimental design. He used the survey technique and the questionnaire instrument. A non-probability sample made up of 40 university teachers was considered as a sample. Processing the information with the support of descriptive and inferential statistics in order to establish how the data does or does not meet the research objectives. The application of the aforementioned Workshop caused positive impacts on intercultural competences in the three dimensions studied, since the statistical results show that the differences in scores between pretest and posttest are significant, proving Jandt’s Theory (1995) in the sense that These competencies are learned and developed, including the intercultural sensitivity of the university teacher.